PERI-URBAN FARMING FOR IMPROVED INCOME: CASE OF FLUTED PUMPKIN PRODUCTION IN SABON GARI LOCAL GOVERNMENT AREA OF KADUNA STATE, NIGERIA. - SHUAIBU, H.; YAKUBU , A.; HASSAN , A. A.; EMMANUEL , B. H. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The study assessed peri-urban farming for improved household income in the case of fluted pumpkin production in Sabon Gari Local Government Area of Kaduna State, Nigeria. The objectives of the study were to determine the profitability of pumpkin leaf, determine the factors that influence the profitability and identify the constraints the producers faced. Purposive sampling was used to select 2 wards from the 11 wards in the area due to concentration of fluted pumpkin production in the area. Three peri-urban towns were then selected from each ward using random sampling technique. Twenty (20) fluted pumpkin farmers from each town were randomly selected. This gave a total of 120 respondents. Interview schedule was used for data collection. Descriptive statistics, gross margin and multiple regression analysis were used for analysis. A gross margin of N16,480 and a return per investment (RNI) of N 1.98 were realized by the farmers in a year. The results of the regression analysis indicate that sex (β = -85131.925, p < 0.01), marital status (β = -67562.489, p < 0.01), household size (β = -2402.679, p < 0.05) and years of experience (β = 31825.687, p < 0.01) were the socio-economic factors that significantly influenced the level of profit from pumpkin production. The results also showed that about 32% of the respondents encountered the problem of inadequate rainfall, another 32% also reported financial constraint and 21% perceived low productivity as a problem. It was concluded that fluted pumpkin production in peri-urban area was profitable though producers faced some production constraints.